PEMOLAAN KOMUNIKASI TRADISI UPACARA ADAT PERNIKAHAN MASYARAKAT MELAYU KAMPAR (Studi Etnografi Komunikasi Pada Tradisi Upacara Adat Pernikahan Masyarakat Melayu Kampar Di Desa Muara Mahat Baru Kecamatan Tapung Kabupaten Kampar Provinsi Riau - Annisa "; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tradition wedding ceremonies Kampar Malay community in the village of Muara Mahat Baru is a tradition that has several stages in the implementation of wedding ceremonies and there are linguistic skills, social interaction, and culture. So the purpose of this study was to determine the communicative situation, communicative events, and follow-communicative in communication patterning tradition Kampar Malay wedding ceremonies in the village of Muara Mahat Baru Tapung District of Kampar regency of Riau Province. This study used qualitative methods to approach Ethnography of Communication. The location study was conducted in the village of Muara Mahat Baru Tapung District of Kampar district in Riau province. Informants in this study amounted to five people, two of them existed as ninik mamak chiefs, two people mamak cornerstone, and the mother of the bride are selected using purposive sampling technique. Techniques of data collection is done through observation, interviews, and documentation. Research results obtained by researchers showed that the communicative situation there are two phases to be carried out, namely, the situation before the wedding and during the wedding. Communicative events based on the type of events to accept the proposal to deliberate on the part of men and gave permission and blessing. The topic achieve consensus and requested permission words ninik Mamak. The function and purpose provide an opportunity for both sides to prepare for the wedding and tell that kid nephew is getting married. The setting of all stages of the marriage was the girl's family home. Participants entire extended family on both sides. Message forms of verbal and non-verbal messages. Fill in all the stages of his message has the goal of a harmonious union of two families. Follow-communicative form of advice and instruction in traditional wedding ceremonies performed by ninik mamak tribal chief who respected and admired for proficient and fluent in spoken words. Keywords: traditional wedding ceremony, com